Effect of Encoding on Prospective Memory - Chen, Youzhen; Zhang, Manman; Xin, Cong; Guo, Yunfei; Lin, Qin; Ma, Zhujun; Hu, Jinhui; Huang, Weiting; Liao, Qianfang (Frontiers in Psychology, 2022)
Event-based prospective memory (ProM) refers to remembering to execute planned actions in response to a target ProM cues. Research has demonstrated that visual encoding modality influence ProM, encoding of visual cues is more commonly used as compared to auditory cues. This study examined the effects of encoding modality (visual vs. auditory), cue-encoding specificity (specific cue vs. non-specific cue), and encoding modes (standard vs. implementation intention) on event-based ProM tasks. In Experiment 1, cue specificity and encoding modality were manipulated as within-groups and between-groups variable. Results revealed facilitative effect of cue specificity on ProM performance. Also, with respect to encoding modality, participants showed better performance when receiving auditory instructions compared to visual encoding condition. In Experiment 2, as in Experiment 1, cue specificity and encoding modality were manipulated. Adding encoding modes as the new between-groups variable. Importantly, there was a significant interaction between encoding modality and encoding modes. Visual implementation intention encoding was a more effective method for improving ProM performance as compared to visual standard encoding. Furthermore, there was a significant interaction between cue-encoding specificity and encoding modes. Implementation intention encoding enhances ProM performance in non-specific cue encoding conditions. Overall, the present study found that (1) auditory encoding modality showed superior ProM performance as compared to visual encoding, although implementation intention had facilitative on ProM performance regardless of the encoding modalities and (2) there was better ProM performance under specific encoding as compared to non-specific encoding and implementation intention had facilitative effect on ProM performance in both the conditions.